Parents’ Perceptions of Student Academic Motivation During the COVID-19 Lockdown: A Cross-Country Comparison - Zaccoletti, Sonia; Camacho, Ana; Correia, Nadine; Aguiar, Cecília; Mason, Lucia; Alves, Rui A.; Daniel, João R. (Frontiers in Psychology, 2020)
The COVID-19 outbreak has ravaged all societal domains, including education. Home confinement, school closures, and distance learning impacted students, teachers, and parents’ lives worldwide. In this study, we aimed to examine the impact of COVID-19-related restrictions on Italian and Portuguese students’ academic motivation as well as investigate the possible buffering role of extracurricular activities. Following a retrospective pretest–posttest design, 567 parents (nItaly= 173, nPortugal = 394) reported on their children’s academic motivation and participation in extracurricular activities (grades 1 to 9). We used a multi-group latent change score model to compare Italian and Portuguese students’: (1) pre-COVID mean motivation scores; (2) rate of change in motivation; (3) individual variation in the rate of change in motivation; and (4) dependence of the rate of change on initial motivation scores. Estimates of latent change score models showed a decrease in students’ motivation both in Italy and in Portugal, although more pronounced in Italian students. Results also indicated that the decrease in students’ participation in extracurricular activities was associated with changes in academic motivation (i.e., students with a lower decrease in participation in extracurricular activities had also a lower decrease in motivation). Furthermore, students’ age was significantly associated with changes in motivation (i.e., older students had lower decrease). No significant associations were found for students’ gender nor for parents’ education. This study provides an important contribution to the study of students’ academic motivation during home confinement, school closures, and distance learning as restrictive measures adopted to contain a worldwide health emergency. We contend that teachers need to adopt motivation-enhancing practices as means to prevent the decline in academic motivation during exceptional situations.